The Recipient Epidemiology and Donor Evaluation Study‐IV‐Pediatric (REDS‐IV‐P): A research program striving to improve blood donor safety and optimize transfusion outcomes across the lifespan. Issue 5 (19th April 2022) - Josephson, Cassandra D.; Glynn, Simone; Mathew, Sunitha; Birch, Rebecca; Bakkour, Sonia; Baumann Kreuziger, Lisa; Busch, Michael P.; Chapman, Kathleen; Dinardo, Carla; Hendrickson, Jeanne; Hod, Eldad A.; Kelly, Shannon; et al.
Abstract: Background: The Recipient Epidemiology and Donor Evaluation Study‐IV‐Pediatric (REDS‐IV‐P) is a new iteration of prior National Heart, Lung, and Blood Institute (NHLBI) REDS programs that focus on improving transfusion recipient outcomes across the lifespan as well as the safety and availability of the blood supply. Study Design and Methods: The US program includes blood centers and hospitals (22 including 6 free‐standing Children's hospitals) in four geographic regions. The Brazilian program has 5 participating hemocenters. A Center for Transfusion Laboratory Studies (CTLS) and a Data Coordinating Center (DCC) support synergistic studies and activities over the 7‐year REDS‐IV‐P program. Results: The US is building a centralized, vein‐to‐vein (V2V) database, linking information collected from blood donors, their donations, the resulting manufactured components, and data extracts from hospital electronic medical records of transfused and non‐transfused patients. Simultaneously, the Brazilian program is building a donor, donation, and component database. The databases will serve as the backbone for retrospective and prospective observational studies in transfusion epidemiology, transfusion recipient outcomes, blood component quality, and emerging blood safety issues. Special focus will be on preterm infants, patients with sickle cell disease, thalassemia or cancer, and the effect of donor biologic variability and component manufacturing on recipient outcomes. A rapid response capability to emerging safety threats has resulted in timely studies related to Severe Acute Respiratory Syndrome Corona Virus‐2 (SARS‐CoV‐2). Conclusions: The REDS‐IV‐P program endeavors to improve donor‐recipient‐linked research with a focus on children and special populations while also maintaining the flexibility to address emerging blood safety issues.